The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1399-3054.2007.00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mitochondrial genome rearrangement on respiratory activity, photosynthesis, photorespiration and energy status of MSC16 cucumber (Cucumis sativus) mutant

Abstract: The effects of changes in mitochondrial DNA in cucumber (Cucumis sativus L.) mosaic mutant (MSC16) on respiration, photosynthesis and photorespiration were analyzed under non-stressed conditions. Decreased respiratory capacity of complex I in MSC16 mitochondria was indicated by lower respiration rates of intact mitochondria with malate and by rotenone-inhibited NADH or malate oxidation in the presence of alamethicin. Moreover, blue native PAGE indicated decreased intensity of protein bands of respiratory chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 65 publications
7
83
0
Order By: Relevance
“…In addition to earlier described effects of mitochondrial mutation on MSC16 leaf carbon and energy metabolism which may affect growth (Juszczuk et al 2007;Szal et al 2009Szal et al , 2010, our data indicate also the possible involvement of apoplastic ROS. ROS level in the apoplast is the result of the activities of plasma membrane-located NADPH oxidases (Low and Merida 1996;Lamb and Dixon 1997) and cell wall-located peroxidases (Wojtaszek 1997).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition to earlier described effects of mitochondrial mutation on MSC16 leaf carbon and energy metabolism which may affect growth (Juszczuk et al 2007;Szal et al 2009Szal et al , 2010, our data indicate also the possible involvement of apoplastic ROS. ROS level in the apoplast is the result of the activities of plasma membrane-located NADPH oxidases (Low and Merida 1996;Lamb and Dixon 1997) and cell wall-located peroxidases (Wojtaszek 1997).…”
Section: Discussionsupporting
confidence: 81%
“…It was reported earlier (Malepszy et al 1996;Juszczuk et al 2007) that MSC16 mutant plants have a considerably slower growth rate and deformed leaves comparing to WT. Cross section of leaves showed that in the mesophyll tissue of MSC16 the area of one cell is often 50-100% greater than of comparable WT leaf cells (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In plants, several complex I mutants have been reported (Gutierres et al, 1999;Karpova and Newton, 1999;Brangeon et al, 2000;Perales et al, 2005;de Longevialle et al, 2007;Juszczuk et al, 2007;Meyer et al, 2009;Haïli et al, 2013). Most of these show delayed growth, but unlike in H. sapiens, the absence of complex I does not cause premature death, possibly due to the presence of bypasses for complex I.…”
mentioning
confidence: 99%
“…4a, c, d). Tobacco CMSII and A. thaliana frostbite1 mitochondrial mutants that lack Complex I, and cucumber MSC16 mutant with lower level of Complex I, display the compensation of Complex I by additional type II NAD(P)H dehydrogenases (Juszczuk et al 2007;Garmier et al 2008;Juszczuk and Rychter 2009;Podgórska et al 2015). The increased capacity of ND in/ex NADH in root mitochondria of S-deficient bean and A. thaliana and in Fe-deficient cucumber may be responsible for rapid adjustment of respiration during prolonged macro-or micronutrient deficiency (Vigani and Zocchi 2010;Juszczuk and Ostaszewska 2011;Ostaszewska et al 2014).…”
Section: Discussionmentioning
confidence: 99%